The HTLV1 oncoprotein Tax and the tumor suppressor p53 bind a common domain of CBP/p300 to mediate transcriptional activation - Scoggin, Kirsten E. Strickler, author; Nyborg, Jennifer, advisor; Mykles, Donald L., committee member; Luger, Karolin, committee member; Stargell, Laurie, committee member (Colorado State University. Libraries, 2003)
Human T-cell leukemia virus type 1 (HTLV-1) is the etiological agent associated with the development of adult T-cell leukemia and encodes a viral transactivator known as Tax. While the precise molecular mechanism by which cellular transformation occurs is unknown, researchers hypothesize that Tax is essential in both viral and cellular gene expression. To activate HTLV-1 transcription, Tax interacts with the cellular protein CREB, and the pleiotropic coactivators CBP/p300. We have characterized a novel and potentially important alternate binding site for Tax on the carboxy-terminal region of CBP/p300 that mediates Tax transcription function. We have determined the minimal binding domain for Tax at the carboxy-terminal binding region, termed CR2, as amino acids 2003 to 2212. A double point mutant of CR2 directed to one of the a-helical motifs in this domain was found to be defective for binding to Tax. We also characterize the region of Tax responsible for interaction with CR2 and show that the previously identified transactivation domain of Tax (amino acids 312 to 319) participates in CR2 binding. The tumor suppressor p53 also recruits the cellular coactivator CBP/p300 to mediate the transcriptional activation of target genes. Previously, p53 has been shown to interact with several regions of CBP/p300, including the C/H3 and KIX domains. We find that p53 also interacts strongly with a smaller region of the CR2 domain encompassing amino acids 2055 to 2150. We show that the same double point mutation targeted to the first a-helical motif in this domain, defective for interaction with Tax, is also compromised for interaction with p53. The observation that both p53 and Tax bind to overlapping regions of CR2 led us to ask whether or not their binding is mutually exclusive. We show that p53 and Tax compete for binding CR2. Thus, Tax disruption of the p53-CR2 complex may be a contributing molecular event in the HTLV-1 transformation pathway. Together, these studies identify novel Tax-interacting and p53-interacting sites on CBP/p300 and extend our understanding of the molecular mechanism of Tax transactivation.
Keywords: molecular biology